Effectiveness of Social Skills Training on Social Adjustment of Elderly People - Zahra Taghinezhad; Mostafa Eghlima; Maliheh Arshi; Paria Pourhossein Hendabad (University of Social Welfare and Rehabilitation Sciences, 2017)
Objective The social adjustments decrease with increasing age, which can have a major impact on the lives of the elderly. According to different studies, using different trainings can increase social adjustment in the elderly group. Therefore, the purpose of the current research is to study the effectiveness of social skills training on social adjustment of elderly.  Materials & Methods The current research is experimental with pre-test and post-test patterns and a control group. The statistical population in this study includes 60 elderly people (36 women and 24 men) of the Elderly Cultural Center in Tehran who were chosen randomly. They were grouped into intervention and control groups. Social skills instruction program was done for all groups undergoing experiments in 8 sessions each with 90 min duration for evaluating the social adjustment of participants before the first session and after the last session. Social adjustment bell (1961) and demographic surveys were filled by participants. Valid and reliable Bell compatibility questionnaire 1378 was measured by Naqshbandi. Reliability coefficient of 0.93 was obtained for the total adjustment, 0.86 for social adjustment, 0.77 for physical health, 0.88 for family harmony, 0.70 for job is emotional adjustment, and 0.85 for compatibility. Bell further validated the construct validity. For data analysis, software SPSS version 16 was used, and descriptive statistics like average, frequency variance, and deductional statistics including U-man Whitney, Leven, Kolmogorov–Smirnov and independent (t) and Dependent (t) and covariance (ANCOVA) examination were used.  Results The result of this research showed that considerable difference can be found between ultimate total social adjustment and each of its subscales, including compatibility of family, emotional, occupational, social and physical health before and after social skills training (P<0.05). Significant differences were found between total and subscales of social adjustment among trained and untrained (P<0.05) people.  Conclusion According to the results of this study, it can be said that holding social skills instruction social work group on social adjustment method is effective among the elderly. The wider use of this type of intervention by specialists in the field of aging can affect well-being and mental health of this group.